T-S Fuzzy-Based Load Frequency Control Design for Nonlinear Power Systems Under Stochastic Actuator Failures - Kuppusamy, Subramanian; Trinh, Hieu; Palanisamy, Muthukumar (2024 Tenth Indian Control Conference (ICC), 2024)
This paper investigates the switched load frequency control techniques for nonlinear power systems together with energy storage system (ESS) subject to actuator faults. In this regard, the faults of actuator are assumed to occur randomly and the fault rates are characterized by stochastic variables that satisfy certain probability conditions. Next, a Takagi-Sugeno fuzzy model is employed to describe the nonlinear characteristics in turbine and governor dynamics of power systems with ESS. The reliable proportional-integral (PI)-type load frequency control is proposed by utilizing the switching approach and Lyapunov-Krasovskii functional with the membership function information, which ensures the asymptotic stability of power system with ESS in the mean-square sense via H_{∞} performance index. At last, the numerical examples are presented to illustrate the superiority of the proposed method.